Morphophysiological responses of Ilex paraguariensis seedlings to different substrates and fertilizations - Thairini C. Zavistanovicz; Maristela M. Araujo; Suelen C. Aimi; Rejane Flores; Álvaro L. P. Berghetti; Gilmar Deponti (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The increasing demand for Ilex paraguariensis St. Hill (yerba mate) by-products generated the need for producing a greater quantity of seedlings and improve their quality. Thus, the objective of this work was to evaluate the efficiency of different substrates combined with base fertilization for Ilex paraguariensis seedlings, through morphophysiological parameters. The experiment was conducted in a completely randomized design, in a 5 x 3 factorial arrangement, and the treatments consisted of five substrate formulations combined with two fertilizers, and a control without fertilization, in November 2013. The I. paraguariensis seedlings produced in the substrate consisted of subsurface soil, cattle manure and charred rice hulls (2:2:1) presented the greatest heights (53.36 cm), stem diameter (6.80 mm), leaf area (692.52 cm2), root dry weight (6.2 g) and total dry weight (16.4 g). The efficiency of the different fertilizations used was similar regarding the seedling growth. The physiological parameters did not differ between treatments. The substrate composed of subsurface soil, manure and charred rice hulls (2:2:1) and fertilization with urea (0.7 g L-1) single superphosphate (8.0 g L-1) and potassium chloride (0.4 g L-1) is recommended for producing I. paraguariensis seedlings.